Influential Factors on Student Satisfaction in High School Sports Education: Unravelling the Roles of Instructor Empathy, System Quality, and Reputation - Hasanuddin; Sopyan Saori; Abdulelah A. Alghamdi; Mochammad Fahlevi (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
The positive impact of sports education programmes in promoting the physical and emotional well-being of students has been firmly proven. However, it is important to comprehend the aspects that lead to student happiness in these programmes in order to guarantee successful execution and favourable results. The present study seeks to examine the impact of instructor empathy, system quality, and reputation on student happiness within the context of sports education programmes offered in high schools in Indonesia. The Privietlab Research Institute administered an online questionnaire to students, resulting in the collection of 364 valid responses. The data was analysed and the study hypotheses were tested using structural equation modelling (SEM). The results of the study indicate that there is a strong and positive relationship between instructor empathy and system quality on reputation. Additionally, reputation was found to have a major beneficial influence on student satisfaction. The findings highlight the significance of instructor empathy, system quality, and reputation in augmenting student satisfaction within sports education programs. Therefore, this research offers significant contributions for educators, school administrators, and policymakers, underscoring the importance of prioritizing these aspects in order to guarantee a superior sports education experience for children in Indonesia.